Práticas de letramentos de estudantes no curso de português para fins acadêmicos na FEAH-UNTL - Soares, Juliana (2025)
This master’s dissertation is linked to the Postgraduate Program in Linguistic Studies of the Federal University of Uberlândia. The collaboration with the International Cooperation Group of Brazilian Universities also supports the realization of this study. It aims to relate the “previous literacy histories of students” (Oliveira, 2016, p. 226) from a group of four students of the Portuguese for Academic Purposes Course, at the Faculty of Education, Arts and Humanities of the National University Timor Lorosa’e with the academic literacy practices experienced by them in that multilingual context. It is intended to understand the academic production of the genre summary by participants. The theoretical basis used encompasses elements of Applied Linguistics (Moita Lopes, 2006; Rojo, 2007), as well as theories of New Literacy Studies/NEL (Street, 1984; 2010; Kleiman, 1995; 2005), Academic Literacies (Lea and Street, 1998; 2014; Fiad, 2011, 2013, 2015, 2016; Fischer, 2007, 2008, Marinho, 2010; Oliveira, 2009, 2016; Zavala, 2010) and discursive genres (Bakhtin, 2011). The research is justified by the complexity of writing academic genres in a setting where participants in the FEAH-UNTL CPFA, in collaboration with Leitorado Guimarães Rosa, are asked to read and write academic genres, such as the summary, in Portuguese. This study employs a qualitative methodology (Paiva, 2019), with an ethnographic nature (Lillis, 2008). Semi-structured online interviews were conducted with students to generate information, conducted in the two official languages of East Timor, Tetum and Portuguese. Additionally, participants produced writing diaries about the course, which were sent to me individually. At the end of the course, with the support of Timorese teachers, CPFA participants prepared academic summaries, which were sent to me for analysis and discussion. The research, based on written documents about the course and online interviews, revealed a range of literacy experiences shared by students. These experiences, include reading and writing in school, university and family contexts, can be mostly categorized as vernacular practices. The results indicate that students face significant challenges, especially in interpreting academic texts, writing summaries and using specialized vocabulary appropriately, as well as in the structure of the Portuguese language. Despite these complexities, the evidence shows that students value the support of their teachers to integrate into the academic training process. Furthermore, the participants' opinions reflect a more traditional models on study skills and academic socialization for academic writing, centered on language proficiency and with little emphasis on social elements, such as identity, authority, and power relations in the academic environment, as highlighted by Lea and Street (2006; 2014). However, as underlined by Fiad (2013a), based on Bakhtin (1997), and by Guimarães (2018), who is also based on him (Bakhtin, 2011) and his circle, academic writing can be perceived as an environment of (re)writing and negotiation of meanings, in which students not only follow norms, but also create their own voices and assume themselves as “creator-authors”. In this context, the summaries of the four CPFA participants, despite the challenges in using the Portuguese language, reveal emerging practices of discursive engagement, reflecting how students interact with texts. They attributed meanings to their texts, and they developed their authorial identities in a multilingual environment full of complexities.